CATECHOLAMINE ASSAY BY RADIOENZYMATIC METHOD - A PROTOCOL - Nasim Karim; Joshua R. berlin (Journal of the Dow University of Health Sciences, 2008)
Catecholamines are a group o f compounds identified by the catechol nucleus. The significant catecholamines found naturally in the body are epinephrine, nor- epinephrine and dopamine. They are found in various tissues o f the body like brain, adrenals, GIT, blood, urine and cerebrospinal fluid in picogram quantities. Knowledge of catecholamines is im portant in the diagnosis and managem ent o f pheochromocytoma, CNS tumours like neuroblastoma, Diabetes mellitus, hypertension, coronary disease, angina pectoris, myocardial infarction etc. A nalytical techniques for determ ination o f catecholamines have been developed w hich are generally based upon the use o f isolated enzym e catechol-O -m ethyltransferase (COM T) to transfer a radioactive methyl group from S-adenosyl-L-methionine (SAM) to an endogenous catecholamine acceptor m olecule to form a radioactive O-m ethyl catecholam ine derivative. This article gives a basic out line of the catecholam ine assay along w ith a sim plified protocol that can be easily perform ed in the laboratory.